2010
DOI: 10.1159/000264649
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of IgG Antibodies against Food Antigens in Crohn’s Disease: A Double-Blind Cross-Over Diet Intervention Study

Abstract: Background: Environmental factors are thought to play an important role in the development of Crohn's disease (CD). Immune responses against auto-antigens or food antigens may be a reason for the perpetuation of inflammation. Methods: In a pilot study, 79 CD patients and 20 healthy controls were examined for food immunoglobulin G (IgG). Thereafter, the clinical relevance of these food IgG antibodies was assessed in a double-blind cross-over study with 40 patients. Based on the IgG antibodies, a nutritional int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 65 publications
1
47
0
4
Order By: Relevance
“…Moreover, considering that as dietary habit is a significant risk factor for yeast sensitivity, we may correlate this difference with the nature of Turkish diet which mainly bases on grain and excessive consumption of fermented foods and sugar. In a study, 84% and 83% of the patients showed highes intolerance to prossessed cheese and yeast, respectively [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considering that as dietary habit is a significant risk factor for yeast sensitivity, we may correlate this difference with the nature of Turkish diet which mainly bases on grain and excessive consumption of fermented foods and sugar. In a study, 84% and 83% of the patients showed highes intolerance to prossessed cheese and yeast, respectively [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 Similarly, high levels of the IgG4 food antibodies are also observed in patients with inflammatory bowel disease, where intestinal mucosal permeability is known to be increased. 24,25 Some studies have demonstrated that food-specific IgG4 antibody-guided exclusion diet may be effective in alleviating IBS symptoms. 26,27 The IgG4 antibody-guided exclusion diet affects various symptoms including abdominal pain or discomfort, stool shape, diarrhea frequency, and general feelings of distress.…”
Section: Discussionmentioning
confidence: 99%
“…There are at least seven sham-controlled dietary advice RCTs investigating the effect of 290 whole diet interventions reported in the literature (Table 2) (38)(39)(40)(41)(42)(43)(44)(45) . Most evaluate the effect of (40) , the patient's usual diet (41) , is relatively arbitrary (38,39,42,43) or excludes another 295 dietary component (44) .…”
mentioning
confidence: 99%